Evaluation of Anterior Decompression Surgical Outcomes of Proximal‐Type Cervical Spondylotic Amyotrophy: A Retrospective Study - Chang‐bo Lu; Zhen‐sheng Ma; Jin‐bo Hu; Xiao‐jiang Yang; Wei Wei; Yang Zhang; Wei Lei (Orthopaedic Surgery, 2020)
Objective To investigate the efficiency of anterior decompression on the proximal‐type cervical spondylotic amyotrophy patients. Methods This was a retrospective analysis. From January 2014 to November 2017, 21 patients with proximal‐type cervical spondylotic amyotrophy (CSA) underwent anterior decompression. There were 15 males and 6 females, aged 35–73 years with an average of 51.62 years. All the patients underwent surgery of anterior decompression (ACDF or ACCF). Among them, 12 patients underwent C4/5 single level ACDF, eight patients underwent C4/5 and C5/6 double level ACDF, and one patient underwent C5 anterior cervical corpectomy decompression and fusion surgery. Preoperative and postoperative clinical and radiologic parameters were assessed. The clinical examinations were reviewed, including muscle strength, neck disability index (NDI) score, cervical Japanese Orthopaedic Association (JOA) score, and improvement rate of manual muscle test (MMT) at the last follow‐up. Preoperative spinal cord or nerve impingement was assessed by magnetic resonance imaging (MRI) or computed tomography (CT) myelography. Postoperative lateral X‐ray radiographs were performed every 3 months after the surgery. Results Severe preoperative muscle atrophy of the deltoid or biceps muscles occurred in 21 patients included in the study. All of them involve impingements of the ventral nerve root and/or the anterior horn according to MRI and CT myelography. The preoperative duration of symptoms averaged 8.4 months. The average follow‐up for all patients was 13.2 months. At the final follow‐up, all patients showed statistically significant improvements in muscle strength and NDI scores (P < 0.05, P < 0.05). For the deltoid muscles force and C‐JOA scores, the average improvement rates were 66.49% ± 10.04% and 62.23% ± 9.23%, respectively. With respect to MMT, 12 proximal‐type patients were graded excellent, six were good, and three were fair, and the overall improvement rate was 85.7%. Conclusions For proximal‐type CSA patients with cervical radiculopathy, earlier anterior decompression surgery can achieve satisfactory results by significantly improving a patient's muscle strength and relieving compression symptoms.